Mechanical property evaluation of natural fiber coir composite - Harish, S.; Peter Michael, D.; Bensely, A.; Mohan Lal, D.; Rajadurai, A.
The fiber which serves as a reinforcement in reinforced plastics may be synthetic or natural. Past studies show that only artificial fibers such as glass, carbon etc., have been used in fiber-reinforced plastics. Although glass and other synthetic fiber-reinforced plastics possess high specific strength, their fields of application are very limited because of their inherent higher cost of production. In this connection, an investigation has been carried out to make use of coir, a natural fiber abundantly available in India. Natural fibers are not only strong and lightweight but also relatively very cheap. In the present work, coir composites are developed and their mechanical properties are evaluated. Scanning electron micrographs obtained from fractured surfaces were used for a qualitative evaluation of the interfacial properties of coir/epoxy and compared with glass fiber/epoxy. These results indicate that coir can be used as a potential reinforcing material for making low load bearing thermoplastic composites.
Keywords: EPOXY; FRACTOGRAPHY; COIR; SCANNING ELECTRON MICROSCOPY